Deceleration performance comparison for passenger car under on-road and off-road driving condition - Mohd Khairil, Asri Kamaluddin (2010)
In deceleration, there are many factors that influent the deceleration performance. The factors are like brake system and the road condition. Other than that, how the driver pressed the brake pedal also influenced the deceleration performance and also the safety during braking. This must be considered during designed the brake system of the car. The objectives of this project are to collect the data of the passenger car during decelerates using the UMP’s test car under on-road and off-road driving condition and to analyze the deceleration performance of passenger car for difference deceleration test. This report describes the few type of deceleration by run the test. The test was divided into two sections which are on road and off road. For the on road test, the initial speed of the car before decelerate was varies and control the stopping distance. Base on the theory, the higher the initial speed of the car, the longest time and distance needed to stop safely but for this test, the stopping distance is constant so that the stopping time will decrease if the initial speed is increase. Other than that, the brake system also needs to absorb greater energy and power if the car decelerates from the high speed. For the off road test, the stopping time and stopping distance want to be study base on the initial speed of the car. Finally, some calculations need to be performed using related formulas and equations to know the difference between all the decelerations types. Some graphs was plotted to show the trends and pattern of the result. The results concluded that the braking techniques and ways to reduce the car speed will affect the stopping time, stopping distance, and power and energy absorb by the brake system. Therefore, the road condition also is the main factor that influent the deceleration performance of the passenger car. The results indicate difference deceleration behavior for passenger car under various speed in on-road and off-road condition, which is an important study to develop difference braking techniques.